The Key Points of Highly Stable Catalysts for Methane Reforming with Carbon Dioxide. Issue 12 (4th September 2013) - Liu, Hong; Guan, Chengyue; Li, Xuan; Cheng, Liyuan; Zhao, Jianbo; Xue, Nianhua; Ding, Weiping
Abstract Stable catalysis performance in long‐term operation is crucial for the wide‐scale industrialization of catalytic processes. The degradation of catalysts is a considerable problem for methane reforming with carbon dioxide, owing to carbon deposition on active sites and/or catalytic supports, and sintering of active components at high temperatures. With base metals and a modified alumina support, the present work has developed highly stable catalysts that operate free of coke formation and sintering of active components. Firstly, homogeneous copper‐nickel alloy nanoparticles (NPs), which have never previously been used for this purpose, were produced and then supported as catalytic centers onto alumina. The CuNi alloy catalyst with a Ni to Cu ratio of unity totally prohibits carbon deposition on active centers, while maintaining high activity for the reforming reaction. Second, the modification of alumina by coating with zirconia before supporting the CuNi alloy, drastically inhibits coke formation on the support, prevents the reaction of Cu in the alloy with alumina at high temperatures, and, therefore, promotes the stability of active alloy NPs. Additionally, after supporting the CuNi alloy NPs on zirconia‐coated alumina, the catalyst was coated with a thinner layer of zirconia to protect the CuNi NPs from sintering, while maintaining high activity. This state‐of‐the‐art catalyst is shown to be highly stable for methane reforming with carbon dioxide at high temperatures and the deactivation constant is calculated to be close to zero in a long‐term operation, even at extremely high space velocity of 120 000 mL g−1 h−1. The results are practically important to develop robust, as well as high performance, catalysts for the relevant reactions.